Assessment of antifungal potential of Acacia auriculiformis extracts against wood decay fungi - POONIA, PAWAN KUMAR; UPADHYA, VINAYAK; M, HANUMANTHA; KUMAR, ANIL (The Indian Journal of Agricultural Sciences, 2022)
The bark and heartwood of Acacia auriculiformis A. Cunn. are known for toxicity against different organisms. The present study aimed to evaluate the efficacy of leaves and saw dust extract of A. auriculiformis against the wood decay fungi like Trametes versicolor and Oligoporus placenta using bioassay method. The experiment was conducted during 2017-18 at College of Forestry, Sirsi (Karnataka) India. Saw dust extract at 0.5% concentration level showed 46.80% and 29.40% inhibition against T. versicolor and O. placenta, respectively. T. versicolor and O. placenta was inhibited by 15.32% and 47.80%, respectively, at 1% concentration of saw dust. The inhibition per cent of saw dust extract against wood decay fungi was higher in comparison to leaf extract. The results indicated that A. auriculiformis saw dust extract can be used further for possible wood preservation in field conditions.